VT

Giải phương trình:

\(\frac{1}{x-1}+\frac{6}{3x+5}=\frac{2}{x+2}+\frac{1}{x+3}\)

BT
13 tháng 6 2020 lúc 18:13

\(\frac{1}{x-1}+\frac{6}{3x+5}=\frac{2}{x+2}+\frac{1}{x+3}\)

\(\Leftrightarrow\frac{3x+5+6x-6}{3x^2+2x-5}=\frac{2x+6+x+2}{x^2+5x+6}\)

\(\Leftrightarrow\frac{9x-1}{3x^2+2x-5}=\frac{3x+8}{x^2+5x+6}\)

\(\Rightarrow9x^3+44x^2+49x-6=9x^3+30x^2+x-40\)

\(\Leftrightarrow14x^2-48x+34=0\)

\(\Rightarrow14x^2-14x-34x+34=0\)

\(\Rightarrow\left(x-1\right)\left(14x-34\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x-1=0\\14x-34=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\x=\frac{17}{7}\end{cases}}}\)

Ngu nên làm dài dòng thôi

Bình luận (0)
 Khách vãng lai đã xóa